Staphylococcus aureus spa type t437: identification of the most dominant community-associated clone from Asia across Europe. (February 2015) - Glasner, C.; Pluister, G.; Westh, H.; Arends, J.P.; Empel, J.; Giles, E.; Laurent, F.; Layer, F.; Marstein, L.; Matussek, A.; Mellmann, A.; Pérez-Vásquez, M.; et al.
Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) belonging to the multilocus sequence type clonal complex 59 (MLST CC59) is the predominant community-associated MRSA clone in Asia. This clone, which is primarily linked with the spa type t437, has so far only been reported in low numbers among large epidemiological studies in Europe. Nevertheless, the overall numbers identified in some Northern European reference laboratories have increased during the past decade. To determine whether the S. aureus t437 clone is present in other European countries, and to assess its genetic diversity across Europe, we analysed 147 S. aureus t437 isolates from 11 European countries collected over a period of 11 years using multiple locus variable number tandem repeat fingerprinting/analysis (MLVF/MLVA) and MLST. Additionally 16 S. aureus t437 isolates from healthy carriers and patients from China were included. Most isolates were shown to be monophyletic with 98% of the isolates belonging to the single MLVA complex 621, to which nearly all included isolates from China also belonged. More importantly, all MLST-typed isolates belonged to CC59. Our study implies that the European S. aureus t437 population represents a genetically tight cluster, irrespective of the year, country and site of isolation. This underpins the view that S. aureus CC59 has been introduced into several European countries, not being restricted to particular geographical regions or specific host environments. The European S. aureus t437 isolates thus bear the general hallmarks of a high-risk clone.